Analisa Penyebab Kegagalan Proyek Ditinjau dari kinerja Waktu, Biaya, dan Mutu - Muhammad Rio; Findia Findia; Achmad Jaya Adhi Nugraha (SENTRI: Jurnal Riset Ilmiah, 2026)
The success of construction projects is commonly assessed by achieving time, cost, and quality targets, whereas failure appears as delays, cost overruns, and noncompliance with technical specifications. Based on construction project management concepts and the time–cost–quality trade-off, this study aims to identify factors influencing the risk of failing to achieve time, cost, and quality objectives in construction projects located in Samarinda City, Kutai Barat Regency, and Mahakam Ulu Regency, and to determine the most dominant factor. A descriptive approach with a survey method was applied to 36 respondents selected using random sampling. The independent variables comprise time, cost, and quality performance, while the dependent variable is project failure. Data were collected through questionnaires and analyzed using Pearson validity tests, Cronbach’s Alpha reliability tests, and percentage calculations of each aspect’s contribution. The results indicate that all items of time (7 items), cost (13 items), and quality (6 items) performance are valid, with correlation coefficients exceeding the critical value of 0.329 and significance levels below 0.05, and reliable, with alpha values of 0.821, 0.901, and 0.849, respectively. The analysis of failure factors reveals that the cost aspect is the most dominant contributor at 50%, followed by quality at 44%, while time contributes 36%. These findings emphasize the need to prioritise budget control and quality assurance systems, supported by effective time management, to reduce the risk of construction project failure in East Kalimantan.